Unraveling the Autonomous Motion of Polymer‐Based Catalytic Micromotors Under Chemical−Acoustic Hybrid Power. Issue 2 (2nd November 2020) - Celik Cogal, Gamze; Das, Pradipta Kr.; Li, Shuangming; Uygun Oksuz, Aysegul; Bhethanabotla, Venkat R.
Abstract : Artificial nano‐ and microswimmers are promising as versatile nanorobots for applications in biomedicine, environmental chemistry, and materials science. Herein, a hybrid micromotor containing a conjugated polymer (poly(3, 4‐ethylenedioxythiophene) (PEDOT), and a catalytic structure composed of platinum (Pt) synthesized using a template‐supported electrochemical deposition process is reported. The movement of this PEDOT/Pt micromotor is characterized under chemical power generated by hydrogen peroxide catalysis, and acoustic power generated by surface acoustic waves (SAWs). The acoustic radiation force acting between the bubbles, the secondary Bjerknes force, is shown to increase the micromotor speed. The movement of the micromotor is precisely controllable using the acoustic field, providing excellent response time and reproducibility over a wide dynamic range. A theoretical model is developed to understand and predict the micromotor propulsion under the hybrid chemical and acoustic power. Predicted micromotor speeds are in excellent agreement with experiment as a function of peroxide fuel concentration, SAW field strength, and SAW frequency. The model allows for design of micromotor geometries and acoustic field strengths to achieve desired speed with excellent on/off control. Abstract : A polymer‐based catalytic (PEDOT/Pt) micromotor is fabricated and its motion is precisely controlled under chemical power generated by H2 O2 catalysis and acoustic power generated by surface acoustic waves, exhibiting excellent response time and reproducibility. The propulsion mechanism of the micromotor is investigated by developing a theoretical model where the model predictions show excellent agreement with the experimental results.